Singapore youth and their idols : celebrity workshop from a media and psychosocial perspective - Deng, Yihan (2008)
This study examines the impact of media exposure (TV, radio, internet, magazines) and psychosocial factors such as self-esteem, emotional autonomy and peer attachment on celebrity worship levels among Singaporean adolescents and includes gender and academic stream of study as control variables.